Image Search Tools in Graphic Design: Insights From Studios in Porto - Sofia Lélis Patricio (2024)
Image search is essential for graphic design work processes. Existing images interact with graphic designers' creative processes in various ways. They can serve as sources of inspiration, facilitate knowledge generation, and provide examples for layout solutions. With the advance of AI-based digital technology, image search tools evolved using algorithms that perform more precise searches based on visual and conceptual similarity. This has increased the possibilities and accelerated the research process for graphic design projects, but this new paradigm also reveals challenges, such as narrowing reflection and creativity, contributing to design fixation and standardisation of graphic design solutions. In this study, we explore the role image search tools plays in graphic design processes. For that, we investigate the perceptions of the work processes of contemporary graphic design studios in Porto. By combining insights from related work and semi-structured interviews, we show a qualitative expression of the data to convey the complexity of the topic, enabling a deep meaning make of the search dynamics in graphic design processes.